Approaches to the Rehabilitation of Dysphagia in Acute Poststroke Patients - Rogus-Pulia, Nicole; Robbins, JoAnne (Seminars in Speech and Language, 2013)
Dysphagia occurs frequently following stroke and may result in serious health consequences including pneumonia, malnutrition, dehydration, and mortality. Prevention of these negative health outcomes requires early identification and treatment of dysphagia. The speech-language pathologist, as part of a multidisciplinary team, holds the primary responsibility for selection of an effective dysphagia rehabilitation program for these patients. Because much research has focused on patients with chronic dysphagia, this review will focus on treatment of patients within the acute phase of recovery poststroke. Although some acute patients may experience transient dysphagia that resolves spontaneously, many will go on to develop chronic dysphagia that may be prevented with provision of early and intensive treatment. An overview of dysphagia following stroke will be provided with information regarding incidence, complications, evaluation, and causes of dysphagia. A thorough discussion of evidence supporting varying approaches to dysphagia rehabilitation will follow with inclusion of several current, novel, and experimental techniques. The importance of the multidisciplinary team and regular reevaluation will be emphasized as well.
Keywords: Dysphagia; stroke; acute; rehabilitation; evidence